Housing Precariousness and the Wellbeing of Australian Adults - Hewton, Jack (Curtin University, 2021)
This thesis generates a comprehensive evidence base that offers an up-to-date picture on the links between housing precariousness and wellbeing. Housing precariousness consists of four dimensions – tenure insecurity, unaffordable housing, unsuitable housing and insecure neighbourhoods. Private renting, an aspect of tenure insecurity, had the greatest impact on wellbeing, associated with reduced life satisfaction. The findings highlight the need for fixed and long-term leases, removing without-grounds evictions and policies that provide housing security for low-income individuals.